Guidance on Field Study Orientation to the Development of Graduate Competence - Hartanto, Benny; Aditya Pratama, Himawan; Dekanawati, Vivid; Kristianto, Lukas; Astriawati, Ningrum; Pratama, Wegig (IJCS: International Journal of Community Service, 2024)
Field study orientation guidance is intended as an effort to develop elements of behaviour and ability in good learning to produce positive abilities, high learning motivation, and high skills and effective learning skills in students through integrative activities in the learning process in the field to develop the competence of study program graduates. The purpose of this community service is to conduct field study orientation guidance to develop graduate competence on the Km Lawit Ship to Semarang-Karimun. The implementation method used in this service is direct guidance in the field by providing direction, guidance techniques, and evaluating graduate competence development efforts. Field study orientation numbered 100 people, with details of study programs: nautical studies totalling 13 people, ship machinery study program totalling 15 people, marine transportation management study program totalling 40 people, and transportation study program totalling 32 people. The result of this service is the average field study orientation guidance activities to develop the competence of graduates, who answered strongly agreeing by 84.40%, agreeing by 11.80%, neutral by 3.00%, disagreeing by 0.80%, and disagreeing by 0.00%.